APPsolutely trustworthy? Perceptions of trust and bias in mobile apps. - Kaye, Barbara K.; Johnson, Thomas J. (Atlantic Journal of Communication)
Almost all news media, political organizations and candidates now have a dedicated app that provides superior visibility and readability on a mobile device than a website. Mobile apps figure predominately in news consumers' lives, making it crucial to understand if users view app information as trustworthy and biased. With the proliferation of apps on tablets and smartphones, perceptions of app trustworthiness and bias are important to study, especially in times of flagging media trust and use. Comparisons of perceptions of trustworthiness show that apps are significantly more trusted than social media (political blogs, Facebook, Twitter, video sites, and social news sites), but significantly below broadcast and cable television news (Fox News, CNN, MSNBC), print media (newspapers, news magazines), and talk and news radio. Trust in apps is also significantly predicted by reliance on apps. Mobile apps are also deemed significantly less biased than social media, Fox News, CNN, MSNBC, and talk radio. Further, perceptual bias of political blogs and talk radio negatively predict trust in apps, but bias in CNN, newspapers, news magazines, and news radio is associated with high trust in apps.